2020
DOI: 10.1016/j.strueco.2020.03.010
|View full text |Cite
|
Sign up to set email alerts
|

A quarter century of inflation targeting & structural change in exchange rate pass-through: Evidence from the first three movers

Abstract: This study analyses the implications of Inflation Targeting (I.T.) for the Exchange Rate Pass-Through (ERPT) to inflation and trade balance by focusing on the first three movers i.e. New Zealand, UK and Canada. Drawing on the monthly data from October 1976 to September 2017, we employ a TVSVAR framework. Our key findings suggest that there is significant evidence of time-variation in the ERPT to inflation and trade balance in all three countries. Contrary to the notion that the ERPT to inflation has decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 71 publications
1
13
0
1
Order By: Relevance
“…Thirdly, the real effective exchange rate found to have a significant impact in all three countries suggesting the exchange rate pass-through to inflation expectation. These findings are in line with the study by Forbes (2016); Forbes et al (2017Forbes et al ( , 2018; Nasir et al ( , 2020a; Nasir & Vo (2020) which have argued that ERPT to inflation persists regardless of inflation targeting. More specifically, our findings are in line with Nasir et al (2020a) which suggested significant ERPT to inflation expectation in the Czech Republic.…”
Section: Inflation Expectations -N-ardlsupporting
confidence: 92%
“…Thirdly, the real effective exchange rate found to have a significant impact in all three countries suggesting the exchange rate pass-through to inflation expectation. These findings are in line with the study by Forbes (2016); Forbes et al (2017Forbes et al ( , 2018; Nasir et al ( , 2020a; Nasir & Vo (2020) which have argued that ERPT to inflation persists regardless of inflation targeting. More specifically, our findings are in line with Nasir et al (2020a) which suggested significant ERPT to inflation expectation in the Czech Republic.…”
Section: Inflation Expectations -N-ardlsupporting
confidence: 92%
“…There is a substantial amount of literature on the impact of exchange rate dynamics on inflation, including the evidence on the UK (for instance, see Menon, 1995;Goldberg and Knetter, 1997;Hänninen and Toppinen, 1999;Campa and Goldberg, 2005;Choudhri and Hakura, 2006;Bache, 2006;Mumtaz et al, 2006;Bhattarai, 2011;Wimanda et al 2011;Burnstein and Gopinath, 2013;Forbes, 2014;Forbes, 2016;2015a;Yildirim and Ivrendi, 2016;Nasir and Simpson, 2018;Nasir and Vo, 2020;Nasir et al 2020aNasir et al , 2020b. Despite the substantial evidence on the subject, the existing models and estimates have substantial limitations and particularly when it comes to UK data on the exchange rate pass-through there are major divergences between the prevailing wisdom on the nexus between inflation and exchange rate and what is actually observed.…”
Section: Exchange Rate Pass-through To Inflationmentioning
confidence: 99%
“…Therefore, monetary policy must continue to take these fluctuations into account to ensure that inflation expectations remain well-anchored. In fact, contrary to the Mishkin (2008) idea that the exchange rate pass-through might have reduced, Forbes (2015a), Nasir and Simpson (2018) and Nasir and Vo (2020) raised the possibility that exchange rate pass-through may be occurring faster today than in the past, accelerating the immediate impact on inflation. The similar argument was made by Fisher (2015) suggesting that the Federal Reserve Board assumes a substantially faster rate of pass-through to inflation.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations